Initial Validation and Refinement of the Hierarchical Inventory of Personality for Children in the Australian Context. (16th March 2016) - Watt, Dianne; Hopkinson, Laura; Costello, Shane; Roodenburg, John
Abstract : Objective: Amelioration of cross‐cultural and cross‐language impacts on scale validity should be of concern to the researcher. The Hierarchical Personality Inventory for Children, (HiPIC), a 144‐item Five‐Factor Model Flemish personality scale, is both a cross‐cultural and language scale in Australia. The present study is a mixed method validation study of the translated version of the HiPIC for use within the Australian context. Method: Cognitive interviewing of 10 end‐users of the HiPIC identified potentially confusing items. Alternate items were generated by a team of developmental psychologists. A further sample of parents/carers of children aged 5–14 years ( N = 399) completed the HiPIC items. Iterative single‐factor principal component analyses of the internal structure of facets were used to select psychometrically defensible items for an adapted HiPIC or HiPIC‐A. The hierarchical model of the HiPIC‐A was then confirmed against a Flemish HiPIC sample using Procrustes rotation, with external validity considered by comparison to the Strengths and Difficulties Questionnaire. Results: The resulting HiPIC‐A, reduced to 124 items including 13 adapted items, achieved sound internal consistency and high total congruence (0.98) with the Flemish sample. Regression against the Strengths and Difficulties Questionnaire demonstrated further support for external validity of the HiPIC‐A. Conclusion: The mixed method design was an effective approach to a cross‐language cultural adaptation and validation of the HiPIC, confirming the robust nature of the HiPIC model. The potential for the adapted HiPIC‐A to identify adaptive and maladaptive developmental trajectories in Australian children has important implications for practice and further research. On‐going validation is outlined.